Cdc25 and Wee1: analogous opposites? - Kornbluth Sally; Perry Jennifer A (Cell Division, 2007)
Abstract Movement through the cell cycle is controlled by the temporally and spatially ordered activation of cyclin-dependent kinases paired with their respective cyclin binding partners. Cell cycle events occur in a stepwise fashion and are monitored by molecular surveillance systems to ensure that each cell cycle process is appropriately completed before subsequent events are initiated. Cells prevent entry into mitosis while DNA replication is ongoing, or if DNA is damaged, via checkpoint mechanisms that inhibit the activators and activate the inhibitors of mitosis, Cdc25 and Wee1, respectively. Once DNA replication has been faithfully completed, Cdc2/Cyclin B is swiftly activated for a timely transition from interphase into mitosis. This sharp transition is propagated through both positive and negative feedback loops that impinge upon Cdc25 and Wee1 to ensure that Cdc2/Cyclin B is fully activated. Recent reports from a number of laboratories have revealed a remarkably complex network of kinases and phosphatases that coordinately control Cdc25 and Wee1, thereby precisely regulating the transition into mitosis. Although not all factors that inhibit Cdc25 have been shown to activate Wee1 and vice versa, a number of regulatory modules are clearly shared in common. Thus, studies on either the Cdc25 or Wee1-regulatory arm of the mitotic control pathway should continue to shed light on how both arms are coordinated to smoothly regulate mitotic entry.